Synthesis of N-Cbz-Substituted β3-Amino Ketones Utilizing 4-Substituted 1,3-Oxazinan-6-ones - Sleebs, Brad E.; Nguyen, Nghi H.; Hughes, Andrew B. (Synlett, 2013)
Stereoselective synthesis of N-Cbz-substituted β-amino ketones exploiting the versatile 1,3-oxazin-6-one scaffold is reported. The 4-substituted 1,3-oxazinan-6-ones were enolized and acylated diastereoselectively by addition of various acyl halides. Acidic decarboxylation was then employed to smoothly transform the 5-acylated products to chiral β-amino ketones. This methodology further highlights the utility of the 1,3-oxazinan-6-one as a scaffold to access valuable synthons that are used in the peptidomimetic field.
Keywords: ketones; amino acids; acylation; ring opening; oxazinanones